Revealing diagnostic characters through morphological evolution in cleptoparasitic spider wasps (Hymenoptera, Pompilidae, Ceropales). (16th March 2022) - Waichert, Cecilia; Rodriguez, Juanita; Lelej, Arkady S.; von Dohlen, Carol D.; Pitts, James P.
Abstract: Spider wasps (Hymenoptera: Pompilidae) cleptoparasites, such as Ceropales Latreille, have evolved the ability to steal the spiders from other pompilids. This behaviour is often observed with morphological adaptations that might mislead taxonomic decisions due to convergence. For instance, four subgenera, Bifidoceropales Wolf, Ceropales s. str., Hemiceropales Wolf and Priesnerius Móczár and six species‐groups are recognized within Ceropales ; all with doubtful identification. We studied species of Ceropales in light of molecular and morphological characters to delimit lineages and to test the applicability of morphological traits in diagnosing them. We used the molecular nuclear markers long‐wavelength rhodopsin and 28S ribosomal RNA, and the mitochondrial Cytochrome C Oxidase I available at Genebank to reconstruct Bayesian and maximum likelihood phylogenetic trees. Our results disagree with the current subgeneric classification. We found that fore wing venation and the shape of the female posterior metasomal segments are key characters to differentiate lineages. We discuss morphological evolution of the sting apparatus using ancestral state reconstructions; and we propose Bifidoceropales as a junior subjective synonym of Ceropales s. str., whereas Priesnerius, stat. resurr. and Hemiceropales are redefined based on male and female morphological traits. This study raises important concerns, from the validity of diagnostic characters currently used to identify cleptoparasite spider wasps—and taxa with habitat constraints leading to homoplasies. Taxonomy can benefit from the reconstruction of ancestral traits by revealing reliable diagnostic characters. Moreover, our investigation provides a framework for evolutionary studies on hymenopteran cleptoparasitoids and sets the basis for future phylogenomic investigations on Ceropales by opening new perspectives for taxonomic acts and guiding taxonomic sampling efforts.